Tradisi Buang Jong: Perspektif Moderasi Beragama di Desa Tanjong Tinggi - Haminudin, Haminudin; Pandawa, Rian; Husnayaini, Ihda (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2023)
This article aims to describe the history, process and form of the Buang Jong traditional ceremony tradition from the perspective of religious moderation. This research was conducted using qualitative method with descriptive analysis. Buang Jong is a traditional ceremony carried out for generations by the Sawang tribe on Belitung Island to make offerings to the sea god. This is done so that they can get abundant sea products and hope to avoid all kinds of disasters and poverty. The results and discussion of this article are about the application of the value of religious moderation in the Buang Jong tradition. Based on the analysis, the researchers concluded that there needs to be a balanced combination of religious moderation and maintaining the existence of traditional customs passed down from generation to generation. Apart from that, important efforts are also needed to implement religious moderation in carrying out and maintaining existing traditional traditions and not being easily influenced by radical ideas that can cause divisions in society. Tulisan ini bertujuan untuk menggambarkan sejarah, proses, dan bentuk tradisi upacara adat Buang Jong dalam perspektif moderasi beragama. Penelitian ini dilakukan dengan menggunakan metode kualitatif dengan analisis yang bersifat deskriptif. Buang Jong merupakan upacara adat yang dilakukan secara turun-temurun oleh suku Sawang di Pulau Belitung untuk menyampaikan persembahan kepada dewa laut. Hal ini dilakukan agar mereka mendapatkan hasil laut yang melimpah dan memohon agar terhindar dari segala macam malapetaka dan kemelaratan. Hasil dan pembahasan tulisan ini adalah tentang penerapan nilai moderasi beragama pada tradisi Buang Jong. Berdasarkan penganalisis, peneliti menyimpulkan bahwa perlu adanya perpaduan yang seimbang antara moderasi beragama dan mempertahankan eksistensi adat tradisi turun-temurun. Selain itu, perlu juga adanya upaya penting dalam menerapkan moderasi beragama dalam menjalankan dan mempertahankan tradisi adat yang sudah ada dan tidak mudah terpengaruh dengan paham-paham radikal yang dapat menyebabkan perpecahan di masyarakat.